A multiomic approach to defining the essential genome of the globally important pathogen Corynebacterium diphtheriae - Goodall, Emily C. A. F.; Antunes, Camila Azevedo A.; Möller, Jens; Sangal, Vartul R.; Torres, Von Vergel L.; Gray, Jessica; Cunningham, Adam F.; Hoskisson, Paul A.; Burkovski, Andreas; Henderson, Ian R. (PLoS Genetics, 2023)
Author summaryCorynebacterium diphtheriae causes both toxin-mediated diphtheria and non-toxigenic invasive infections. Despite a vaccine to protect against diphtheria, case numbers for both invasive and diphtherial disease have increased over the last decade. Furthermore, an increase in antibiotic resistant strains are being isolated from patients. It's clear that additional treatment strategies for this organism will be needed in the future. Using high-throughput mutagenesis, this work presents the densest library of mutants for any Corynebacterium sp.. This work identifies the essential genome of C. diphtheriae; an important classification as these genes are often the target of therapeutic intervention. We identify highly conserved genes and species-specific genes unique to pathogens. This data presents an important benchmark and focus for the future development of therapeutic options. Of particular significance is the identification of uncharacterized, conserved proteins within the Diphtheria vaccine.
CRIS-Team WoS Importer:2023-05-26

Beyond diphtheria toxin: cytotoxic proteins of Corynebacterium ulcerans and Corynebacterium diphtheriae - Weerasekera, Dulanthi; Möller, Jens; Kraner, Max; Azevedo Antunes de Oliveira, Camila; Mattos-Guaraldi, Ana Luiza; Burkovski, Andreas (Microbiology, 2019)
Diphtheria toxin is one of the best investigated bacterial toxins and the major virulence factor of toxigenic Corynebacterium diphtheriae and Corynebacterium ulcerans strains. However, also diphtheria toxin-free strains of these two species can cause severe infections in animals and humans, indicating the presence of additional virulence factors. In this study, we present a first characterization of two proteins with cytotoxic effect in corynebacteria. A putative ribosome-binding protein (AEG80717, CULC809_00177), first annotated in a genome sequencing project of C. ulcerans strain 809, was investigated in detail together with a homologous protein identified in C. diphtheriae strain HC04 (AEX80148, CDHC04_0155) in this study. The corresponding proteins show striking structural similarity to Shiga-like toxins. Interaction of wild-type, mutant and complementation as well as overexpression strains with invertebrate model systems and cell lines were investigated. Depending on the presence of the corresponding genes, detrimental effects were observed in vivo in two invertebrate model systems, Caenorhabditis elegans and Galleria mellonella, and on various animal and human epithelial and macrophage cell lines in vitro. Taken together, our results support the idea that pathogenicity of corynebacteria is a multifactorial process and that new virulence factors may influence the outcome of potentially fatal corynebacterial infections.
CRIS-Team WoS Importer:2019-08-13

Cellular and extracellular proteome of the animal pathogen corynebacterium silvaticum, a close relative of zoonotic corynebacterium ulcerans and corynebacterium pseudotuberculosis - Möller, Jens; Schorlemmer, Svenja; Hofmann, Jörg; Burkovski, Andreas (Proteomes, 2020)
Corynebacterium silvaticum is a newly described animal pathogen, closely related to the emerging human pathogen Corynebacterium ulcerans and Corynebacterium pseudotuberculosis, a major pathogen of small ruminants. In this study, proteins of a whole cell and a shaving fraction and the exoproteome of C. silvaticum strain W25 were analyzed as a first proteome study of this species. In total, 1305 proteins were identified out of 2013 proteins encoded by the W25 genome sequence and number of putative virulence factors were detected already under standard growth conditions including phospholipase D and sialidase. An up to now uncharacterized trypsin-like protease is by far the most secreted protein in this species, indicating a putative role in pathogenicity. Furthermore, the proteome analyses carried out in this study support the recently published taxonomical delineation of C. silvaticum from the closely related zoonotic Corynebacterium species.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Exoproteome; LC-MS/MS; Mass spectrometry; Necrotizing lymphadenitis; Secretome; Trypsin-like serine protease; Zoonosis

Complete Closed Genome Sequence of Nontoxigenic Invasive Corynebacterium diphtheriae bv. mitis Strain ISS 3319. - Azevedo Antunes de Oliveira, Camila; Richardson, Emily J.; Quick, Joshua; Fuentes-Utrilla, Pablo; Isom, Georgia L.; Goodall, Emily C.; Möller, Jens; Hoskisson, Paul A.; Mattos-Guaraldi, Ana Luiza; Cunningham, Adam F.; Loman, Nicholas J.; Sangal, Vartul; et al. (Genome Announcements, 2018)

Corynebacterium diphtheriae proteome adaptation to cell culture medium and serum - Möller, Jens; Nosratabadi, Fatemeh; Musella, Luca; Hofmann, Jörg; Burkovski, Andreas (Proteomes, 2021)
Host-pathogen interactions are often studied in vitro using primary or immortal cell lines. This set-up avoids ethical problems of animal testing and has the additional advantage of lower costs. However, the influence of cell culture media on bacterial growth and metabolism is not considered or investigated in most cases. To address this question growth and proteome adaptation of Corynebacterium diphtheriae strain ISS3319 were investigated in this study. Bacteria were cultured in standard growth medium, cell culture medium, and fetal calf serum. Mass spectrometric analyses and label-free protein quantification hint at an increased bacterial pathogenicity when grown in cell culture medium as well as an influence of the growth medium on the cell envelope.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Diphtheria; Host-pathogen interaction; Label-free quantification; Metabolic pathway; Proteomics

Genome sequence of a pathogenic Corynebacterium ulcerans strain isolated from a wild boar with necrotizing lymphadenitis - Busch, Anne; Möller, Jens; Burkovski, Andreas; Hotzel, Helmut (BMC Research Notes, 2019)
OBJECTIVES: Corynebacterium ulcerans can colonize a wide variety of animals and also humans are infected, typically by zoonotic transmission. Symptoms range from skin ulcers or systemic infections to diphtheria-like illness. In contrast, Corynebacterium pseudotuberculosis is widely distributed among herds of sheep, goats and other farm animals, where it causes high economic losses due to caseous lymphadenitis. Here we describe the genome sequence of an atypical C. ulcerans strain isolated from a wild boar with necrotizing lymphadenitis. This strain has similarities to C. pseudotuberculosis. DATA DESCRIPTION: Genome sequence data of C. ulcerans isolate W25 were generated, analyzed and taxonomical relationship to other Corynebacterium species as well as growth properties of the isolate were characterized. The genome of C. ulcerans W25 comprises 2,550,924 bp with a G+C content of 54.41% and a total of 2376 genes.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Emerging pathogen; Genomics; Toxigenic corynebacteria; Zoonotic transmission

Interactions between the Re-Emerging Pathogen Corynebacterium diphtheriae and Host Cells - Ott, Lisa; Möller, Jens; Burkovski, Andreas (International Journal of Molecular Sciences, 2022)
Corynebacterium diphtheriae, the etiological agent of diphtheria, is a re-emerging pathogen, responsible for several thousand deaths per year. In addition to diphtheria, systemic infections, often by non-toxigenic strains, are increasingly observed. This indicates that besides the well-studied and highly potent diphtheria toxin, various other virulence factors may influence the progression of the infection. This review focuses on the known components of C. diphtheriae responsible for adhesion, invasion, inflammation, and cell death, as well as on the cellular signaling pathways activated upon infection.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Apoptosis; Diphtheria; Diphtheria toxin; Mycolic acids; Necrosis; Pyroptosis; Shiga-like toxin

More than a toxin: Protein inventory of Clostridium tetani toxoid vaccines - Möller, Jens; Kraner, Max; Burkovski, Andreas (Proteomes, 2019)
Clostridium tetani is the etiological agent of tetanus, a life-threatening bacterial infection. The most efficient protection strategy against tetanus is a vaccination with the C. tetani neurotoxin, which is inactivated by formaldehyde-crosslinking. Since we assumed that besides the tetanus toxin, other proteins of C. tetani may also be present in toxoid preparations, we analyzed commercially available vaccines from different countries in respect to their protein content using mass spectrometry. In total 991 proteins could be identified in all five analyzed vaccines, 206 proteins were common in all analyzed vaccines and 54 proteins from the 206 proteins were potential antigens. The additionally present proteins may contribute at least partially to protection against C. tetani infection by supporting the function of the vaccine against the devastating effects of the tetanus toxin indirectly. Two different label-free protein quantification methods were applied for an estimation of protein contents. Similar results were obtained with a Total Protein Approach (TPA)-based method and Protein Discoverer 2.2 software package based on the minora algorithm. Depending on the tetanus toxoid vaccine and the quantification method used, tetanus neurotoxin contributes between 14 and 76 % to the total C. tetani protein content and varying numbers of other C. tetani proteins were detected.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Clostridium tetani; Label-free quantification; Neurotoxin; Proteomics; Tetanospasmin; Vaccination

Multi-Omics of Corynebacterium Pseudotuberculosis 12CS0282 and an In Silico Reverse Vaccinology Approach Reveal Novel Vaccine and Drug Targets - Möller, Jens; Bodenschatz, Mona; Sangal, Vartul; Hofmann, Jörg; Burkovski, Andreas (Proteomes, 2022)
Corynebacterium pseudotuberculosis is an important animal pathogen, which is also able to infect humans. An optimal treatment of infections with this pathogen is not available today and consequently, more research is necessary to understand the infection process. Here, we present a combined -omics and bioinformatics approach to characterize C. pseudotuberculosis 12CS0282. The genome sequence of strain 12CS0282 was determined, analyzed in comparison with the available 130 C. pseudotuberculosis sequences and used as a basis for proteome analyses. In a reverse vaccinology approach, putative vaccine and drug targets for 12CS0208 were identified. Mass spectrometry analyses revealed the presence of multiple virulence factors even without host contact. In macrophage interaction studies, C. pseudotuberculosis 12CS0282 was highly resistant against human phagocytes and even multiplied within human THP-1 cells. Taken together, the data indicate a high pathogenic potential of the strain.
CRIS-Team WoS Importer:2023-01-13

Newly isolated animal pathogen corynebacterium silvaticum is cytotoxic to human epithelial cells - Möller, Jens; Busch, Anne; Berens, Christian; Hotzel, Helmut; Burkovski, Andreas (International Journal of Molecular Sciences, 2021)
Corynebacterium silvaticum is a newly identified animal pathogen of forest animals such as roe deer and wild boars. The species is closely related to the emerging human pathogen Corynebac-terium ulcerans and the widely distributed animal pathogen Corynebacterium pseudotuberculosis. In this study, Corynebacterium silvaticum strain W25 was characterized with respect to its interaction with human cell lines. Microscopy, measurement of transepithelial electric resistance and cytotoxicity assays revealed detrimental effects of C. silvaticum to different human epithelial cell lines and to an invertebrate animal model, Galleria mellonella larvae, comparable to diphtheria toxin-secreting C. ulcerans. Furthermore, the results obtained may indicate a considerable zoonotic potential of this newly identified species.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Caseous lymphadenitis; Diphtheria; Diphtheria toxin; Host-pathogen interaction; Macrophage; Vero cells; Zoonosis

Phylogenomic characterisation of a novel corynebacterial species pathogenic to animals - Möller, Jens; Musella, Luca; Melnikov, Vyacheslav; Geißdörfer, Walter; Burkovski, Andreas; Sangal, Vartul (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2020)
The genus Corynebacterium includes species of biotechnological, medical and veterinary importance. An atypical C. ulcerans strain, W25, was recently isolated from a case of necrotizing lymphadenitis in a wild boar. In this study, we have analysed the genome sequence of this strain and compared the phenotypic and virulence properties with other corynebacterial pathogens. Phylogenomic analyses revealed that strain W25 belongs to a novel species along with PO100/5 and KL1196. The latter strains were isolated from a pig and a roe deer, respectively; hence, this species appears to be associated to animals. The isolate W25 is likely a non-toxigenic tox gene bearing strain and may have compromised abilities to adhere to pharyngeal and laryngeal epithelial cells due to potential loss of the gene functions in spaBC and spaDEF pilus gene clusters. A number of corynebacterial virulence genes are present including pld encoding phospholipase D. Therefore, this strain may be able to cause severe invasive infections in animals and zoonotic infections in humans.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Corynebacterium ulcerans; Diphtheria; Non-toxigenic; NTTB; Toxigenic; Virulence; Zoonotic

Proteomics of Bordetella pertussis whole-cell and acellular vaccines - Möller, Jens; Kraner, Max; Burkovski, Andreas (BMC Research Notes, 2019)
Objectives: Bordetella pertussis is the etiological agent of whooping cough, a bacterial infection of especially children, which may be fatal without treatment. In frame of studies to investigate putative effects of vaccination on host-pathogen interaction and clonal distribution of strains, in addition to Corynebacterium diphtheriae and Clostridium tetani toxoid vaccines, also whole-cell and acellular pertussis vaccines were analyzed by mass spectrometry. Data description: LC-MS/MS spectra were generated and analyzed using B. pertussis genome data and proteins present in whole-cell and acellular pertussis vaccines were identified. Subcellular localization of proteins and presence of signal peptides was determined bioinformatically.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Bordetella; DTP vaccine; LC-MS/MS; Mass spectrometry; Pertussis; Vaccination; Whooping cough

Proteomics of diphtheria toxoid vaccines reveals multiple proteins that are immunogenic and may contribute to protection of humans against Corynebacterium diphtheriae - Möller, Jens; Kraner, Max; Sonnewald, Uwe; Sangal, Vartul; Tittlbach, Hannes; Winkler, Julia; Winkler, Thomas; Melnikov, Vyacheslav; Lang, Roland; Sing, Andreas; Mattos-Guaraldi, Ana Luiza; Burkovski, Andreas (Vaccine, 2019)
Introduced for mass immunization in the 1920s, vaccines against diphtheria are among the oldest and safest vaccines known. The basic principle of their production is the inactivation of purified diphtheria toxin by formaldehyde cross-linking, which converts the potentially fatal toxin in a completely harmless protein aggregate, which is still immunogenic. Since in addition to diphtheria toxin also other proteins may be secreted by Corynebacterium diphtheriae during cultivation, we assumed that diphtheria toxoid might not be the only component present in the vaccine. To address this question, we established a protocol to reverse formaldehyde cross-linking and carried out mass spectrometric analyses. Different secreted, membrane-associated and cytoplasmic proteins of C. diphtheriae were detected in several vaccine preparations from across the world. Based on these results, bioinformatics and Western blot analyses were applied to characterize if these proteins are immunogenic and may therefore support protection against C. diphtheriae. In frame of this study, we could show that the C. diphtheriae toxoid vaccines induce antibodies against different C. diphtheriae proteins and against diphtheria toxin secreted by Corynebacterium ulcerans, an emerging pathogen which is outnumbering C. diphtheriae as cause of diphtheria-like illness in Western Europe.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Corynebacteria; Corynebacterium ulcerans; Exoproteome; Mass spectrometry; Proteomics; Secretome; Vaccination